STUDY ON THE EFFECT OF PYRITE, GYPSUM, GRAPHITE ADDITION AND THE EFFECT OF TEMPERATURE ON TIN VOLATILIZATION PERCENTAGE - KEMAL AULIA RAHMAN (NIM : 12514031), DEAN
Tin is one of the most important metal on earth because of its usage. Tin is used for coatings, tinplate, solder, chemicals and metal alloy. In 2016, Indonesia ranked second on world tin production with annual production around 55,000 ton/year, just one place behind China with production around 100,000 ton/year. The main problems in tin smelting is the simultaneously reduction of iron and high tin percentage in slag. One of the methods for extracting tin from slag is fuming method. This research main purposes is to study the effect of pyrite, gypsum and graphite addition and also the effect of temperature on tin volatilization percentage. Slag that was used in this research comes from PT. Timah. The addition of pyrite in this research is 13%, 16%, 18.5%, 22% 30%, 40%, and 54%. Mixing of pyrite and gypsum is done at S/Sn 1.5 with ratio of 70/30, 60/40, 50/50, 40/60, and 30/70. Graphite addition is done at S/Sn 1.5 and ratio of pyrite and gypsum 40:60. Graphite addition is done at 1%, 2%, 3%. The effect of temperature is studied at 1000oC, 1100oC, 1200oC, 1300oC. Fuming process is done at one hour mark. Fuming results were analyzed by using Atomic Absorption Spectroscopy (AAS) and X-Ray Diffraction (XRD). AAS analysis results shows that pyrite addition gives good effect on tin volatilization. The optimum point of pyrite addition is at 22% pyrite with around 71.7 percent tin volatilization. Mixing of pyrite and gypsum did not give significant effect on tin volatilization with the highest tin volatilization is 68.15% at mixing ratio 40:60. Graphite addition will decrease tin volatilization and will help the forming of Fe-Sn compound that will hinder tin volatilization. Temperature will give significant boost on tin volatilization, at 1300oC, tin volatilization reach the highest mark at 97% volatilization. Fuming mechanism with pyrite addition starts with decomposition of FeS2 to FeS. This FeS will react with SnO to form SnS gas. Gypsum will decompose into CaS and SO2 that will react with SnO to form SnS gas. Graphite addition will also form CaS and FeS that will react with SnO and form SnS gas. Graphite addition also reduce FeO and SnO and form Fe-Sn compound.